Digital Leadership and Hospital Performance: The Serial Mediating Roles of Employee Engagement and Job Satisfaction - Sukmo Hadi Nugroho; Diah Pranitasari; Meldasari Said (Goodwood Publishing, 2026)
Purpose: This study examines how digital leadership and Strategic Human Resource Management (SHRM) influence hospital performance through employee engagement and job satisfaction. Using SHRM and employee behavioral perspectives, the study develops an integrated framework linking digital leadership, talent management, career development, employee well-being, performance management, and HR analytics to organizational performance. Research Methodology: A quantitative explanatory design was employed using survey data from 200 hospital employees in Jakarta. The model was analyzed using Partial Least Squares structural equation modeling (PLS-SEM) to test the direct and serial mediation effects. Results: The results show that digital leadership (β = 0.29), talent management and career development (β = 0.33), and employee well-being (β = 0.31) significantly enhance employee engagement. Engagement strongly affects job satisfaction (β = 0.74) and performance management and HR analytics outcomes (β = 0.45), whereas job satisfaction further improves performance (β = 0.34). A significant serial mediation mechanism was confirmed, with engagement and job satisfaction jointly transmitting the effects of strategic HR practices on performance. The model demonstrates strong explanatory power (R² = 0.61 for engagement; R ² = 0.68 for performance). Conclusions: The study concludes that Hospital performance in the digital era depends on the alignment of digital leadership, talent development, employee well-being, and HR analytics-based performance systems. Limitations: The cross-sectional design and self-reported data limit causal inference, suggesting the need for future longitudinal and multi-source research. Contributions: This study contributes to the literature by proposing an integrated SHRM framework and validating a serial mediation model in healthcare settings.